Efektivitas Pemakaian Sikat Gigi Timer Dua Menit Terhadap Penurunan Skor Plak Gigi pada Anak Usia 7-8 Tahun - Lisa Prihastari; Asmara Saffikri (Andalas Dental Journal, 2022)
Background: The global prevalence of dental caries is still high and reach 60 to 90% of school children. Dental caries is caused by dental plaque that can be prevented by brushing teeth. ADA recommended two minutes as duration of brushing teeth, but many Indonesian children haven’t reached that standard. Purpose: Knowing the effectiveness of two minutes toothbrush timer and conventional toothbrush to the plaque accumulation. Methods: This was an experimental study using pre and post-test group control with single blind design. Amount of 40 students aged 7-8 years divided to two group (control and intervention) using simple random sampling technique. The respondens was instructed to brushing teeth (Bass method) for two minutes, then the plaque index was measured by Löe & Silness method. Results: Independent t-test results showed the significant differences (mean of plaque index reduction was higher in toothbrush timer group compared to conventional toothbrush group). However, there was no significant difference at the last visit. Conclusion: Using two minutes toothbrush timer is not effective to reduce plaque accumulation. With the increasing of children’s ability in brushing teeth, making the use of timer toothbrush or without timer is useful in reducing plaque.